O teatro como caminho para conhecimento e transformação na/da sala de aula: experiência com ensino/aprendizagem em escolas públicas - Cunha, Darlene Maria Medeiros Garcez (2018)
This article takes an approach from the theater as a pedagogical action in the classroom, able to aid the educational process in order to impress on it greater meanings. Thus, we analyze the contribution of the field of Art teaching in the development of the fifth year of elementary school. Through this text, it is intended to stimulate the discussion about the potential of theater in the Arts classes as a possibility to rethink the practices of bullying and the culture of stereotypes in the school environment. For this, we opted for Augusto Boal's Theater of the Oppressed techniques, which led to transformations in the expansion of knowledge, sensitivity and tolerance of students.